Shifting Research with International Students Away from Documenting Experiences Toward Transforming Practices - Mittelmeier, Jenna (International Higher Education, 2025)
<h3 id="this-article-critically-reflects-on-research-with-international-students-in-higher-education-and-its-preoccupation-with-documenting-experiences-a-substantial-knowledge-base-already-exists-regarding-broad-and-undefined-student-experiences-often-resulting-in-repetitive-findings-a-move-toward-evaluating-and-evidencing-structural-practices-rather-than-individual-experiences-is-suggested-as-a-possible-remedy-urging-scholars-to-reconsider-how-our-work-can-contribute-toward-deconstructing-and-addressing-known-challenges-rather-than-continuing-to-document-them" data-pm-slice="1 1 []">This article critically reflects on research with international students in higher education and its preoccupation with documenting “experiences.” A substantial knowledge base already exists regarding broad and undefined student “experiences,” often resulting in repetitive findings. A move toward evaluating and evidencing structural practices, rather than individual experiences, is suggested as a possible remedy, urging scholars to (re)consider how our work can contribute toward deconstructing and addressing known challenges rather than continuing to document them.